Atrial Fibrosis and Conduction Slowing in the Left Atrial Appendage of Patients Undergoing Thoracoscopic Surgical Pulmonary Vein Isolation for Atrial Fibrillation. (April 2015) - Krul, Sébastien P.J.; Berger, Wouter R.; Smit, Nicoline W.; van Amersfoorth, Shirley C.M.; Driessen, Antoine H.G.; van Boven, Wim Jan; Fiolet, Jan W.T.; van Ginneken, Antoni C.G.; van der Wal, Allard C.; de Bakker, Jacques M.T.; Coronel, Ruben; de Groot, Joris R.
<x xml:space="preserve">Abstract</x> Background— Atrial fibrosis is an important component of the arrhythmogenic substrate in patients with atrial fibrillation (AF). We studied the effect of interstitial fibrosis on conduction velocity (CV) in the left atrial appendage of patients with AF. Methods and Results— Thirty-five left atrial appendages were obtained during AF surgery. Preparations were superfused and stimulated at 100 beats per minute. Activation was recorded with optical mapping. Longitudinal CV (CVL), transverse CV (CVT), and activation times (>2 mm distance) were measured. Interstitial collagen was quantified and graded qualitatively. The presence of fibroblasts and myofibroblasts was assessed immunohistochemically. Mean CVL was 0.55±0.22 m/s, mean CVT was 0.25±0.15 m/s, and the mean activation time was 9.31±5.45 ms. The amount of fibrosis was unrelated to CV or patient characteristics. CVL was higher in left atrial appendages with thick compared with thin interstitial collagen strands (0.77±0.22 versus 0.48±0.19 m/s; P=0.012), which were more frequently present in persistent patients with AF. CVT was not significantly different (P=0.47), but activation time was 14.93±4.12 versus 7.95±4.12 ms in patients with thick versus thin interstitial collagen strands, respectively (P=0.004). Fibroblasts were abundantly present and were associated with the presence of thick interstitial collagen strands (P=0.008). Myofibroblasts were not detected in the left atrial appendage. Conclusions— In patients with AF, thick interstitial collagen strands are associated with higher CVL and increased activation time. Our observations demonstrate that the severity and structure of local interstitial fibrosis is associated with atrial conduction abnormalities, presenting an arrhythmogenic substrate for atrial re-entry.